The equation is

$$\sqrt{3+4\cos^2(x)}=\frac{\sin(x)}{\sqrt 3}+3\cos(x)$$

My solution goes like this

$$ \begin{cases} 3+4\cos^2(x)=\frac{\sin^2(x)}{3}+\frac{6}{\sqrt 3}\sin(x)\cos(x)+9\cos^2(x) \\ \frac{\sin(x)}{\sqrt 3}+3\cos(x) \ge 0 \end{cases} $$

$$3(\sin^2(x)+\cos^2(x))+4\cos^2(x)=\frac{\sin^2(x)}{3}+\frac{6}{\sqrt 3}\sin(x)\cos(x)+9\cos^2(x)$$ $$2\cos^2(x)+\frac{\sin^2(x)}{3}-3\sin^2(x)+\frac{6}{\sqrt 3}\sin(x)\cos(x)=0$$

I multiply by 3 and divide by $\cos^2(x)$:


Let $t=\tan(x)$, then


$$t_1=\frac{7\sqrt 3}{2}$$

$$t_2=\frac{11\sqrt 3}{4}$$

The solutions for $x$ would be arc-tangents of these values.

But the textbook's answer is

$$\color{green}{x_1=\frac{\pi}{3}+2\pi n; x_2=-\arctan\left(\frac{\sqrt 3}{4}\right)+2\pi n}$$

Where did I make a mistake?

P.S. From the textbook

enter image description here

  • 1
    $\begingroup$ Everything was OK until you solved the quadratic at the end ;-) $\endgroup$ – David Aug 28 '15 at 7:18
  • $\begingroup$ @David - Indeed! I'm glad I almost made it. (0: I factored 25 when I should've 5 out of $\sqrt{75}$, getting $25\sqrt{3}$. (0: $\endgroup$ – CopperKettle Aug 28 '15 at 7:36

You made a mistake in factorising the following equation:

$$ 4t^2 -3\sqrt3 t -3 = 0$$

$$ t = \frac{3\sqrt 3 \pm \sqrt{75}}{8}$$



$$\implies t=\dfrac{3\sqrt3\pm\sqrt{(3\sqrt3)^2-4\cdot4(-3)}}{2\cdot4}=\dfrac{3\sqrt3\pm5\sqrt3}8=?$$


The roots of $4 t^2-3 \sqrt{3} t-3$ are $-\frac{\sqrt{3}}{4}$ and $\sqrt{3}$.

A slightly different approach to this problem could be the following:

\begin{align} 3+4\cos^2(x)-\frac{\sin^2(x)}{3}-\frac{6}{\sqrt 3}\sin(x)\cos(x)-9\cos^2(x)=\frac{1}{3} \left(-3 \sqrt{3} \sin (2 x)-7 \cos (2 x)+1\right) \end{align} With this we have $$3 \sqrt{3} \sin (2 x)+7 \cos (2 x)=2\sqrt{19}\sin(2x+y)$$ where $y=\arcsin\frac{7}{2\sqrt{19}}$. Hence the roots can be found as \begin{align} x&=\frac12\Big(\arcsin\frac{1}{2\sqrt{19}}-\arcsin\frac{7}{2\sqrt{19}}\Big)+2\pi n\\ x&=\arcsin\frac{1}{2\sqrt{19}}+\arcsin\frac{7}{2\sqrt{19}}+2\pi n\\ \end{align} now note that \begin{align} \arcsin\frac{1}{2\sqrt{19}}+\arcsin\frac{7}{2\sqrt{19}}&=\arcsin( \frac{1}{2\sqrt{19}}\sqrt{1-\frac{7}{2\sqrt{19}}^2} + \frac{7}{2\sqrt{19}}\sqrt{1-\frac{1}{2\sqrt{19}}^2})\\ &=\arcsin\frac{\sqrt3}{2}\\ &=\frac{\pi}{3} \end{align} Further using $\tan(\alpha+\beta)$ and $\tan(\arcsin x)=\frac{x}{\sqrt{1-x^2}}$ we obtain $$\arcsin\frac{1}{2\sqrt{19}}-\arcsin\frac{7}{2\sqrt{19}}=-2\arctan \frac{\sqrt3}{4}.$$

  • $\begingroup$ I'm afraid I don't understand where $\frac{1}{3} \left(-3 \sqrt{3} \sin (2 x)-7 \cos (2 x)+1\right)$ comes from in the third line of your answer. Is this the result of a transformation? I couldn't get a similar result. $\endgroup$ – CopperKettle Aug 28 '15 at 8:42
  • 1
    $\begingroup$ I use $\sin 2x = 2 \sin x \cos x$ and $\cos 2 x = 2 \cos ^2 x -1$. I also use $\sin^2 x =1- \cos^2 x$. $\endgroup$ – Math-fun Aug 28 '15 at 9:42

The solution of the quadratic equation $4t^2 -3\sqrt3 t -3 = 0$ is wrong. Here, $D = b^2 -4ac$ i.e. D=75.
Hence, $t = \frac{3√3 + or - √D}{2*4}$
$t = \frac{3√3 + 5√3}{8}$
And $t = \frac{3√3 -5√3}{8}$
Hence, $ t = √3, -\frac{\sqrt3}{4}$
Now you will get the desired result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.